Epidemiology of tuberculosis in Minas Gerais, Brazil, between 2013 and 2023 and the impact of the COVID-19 pandemic - do Bem Braga, Renan Clímaco; Meurer, Igor Rosa; D’Carmo Sodré, Maisah Meyhr; de Carvalho, Luciana Debortoli; Marin, Lauro Juliano; Silvério, Marcelo Silva; Garcia, Patrícia Guedes (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB), a disease caused by bacteria of the Mycobacterium tuberculosis complex (MTC), is one of the oldest diseases in human history, and despite several global efforts to reduce case numbers, it remains one of the main causes of death worldwide due infectious agents. This study aimed to analyze the epidemiological trends of tuberculosis in Minas Gerais, Brazil, from 2013 to 2023, with emphasis on the impact of the COVID-19 pandemic on case notification.MethodsBased on epidemiological data obtained from the DATASUS platform, spanning the period from 2013 to 2023, the number of cases, the distribution of confirmed cases by sex, race, education, age group, HIV co-infection and presence of comorbidities such as diabetes, and risk factors like smoking and alcoholism were evaluated. Additionally, the municipalities with the highest number of confirmed cases were identified.ResultsThe research revealed a steady annual rise in TB cases, having the highest number of cases in 2023, with 12.55% of all reported cases. Men between 25 and 54 years of age, with a lower educational level, were the most affected by the disease. Regarding race, the majority of the reported cases were attributed to Brown-skinned people. The co-infection rate involving TB and HIV increased proportionally to the reported cases of TB statewide. Regarding comorbidities and risk factors, diabetes, smoking, and alcoholism composed a large part of the tuberculosis caseload, with alcoholism and smoking being especially related to the male population.ConclusionThe results reinforced the gravity of tuberculosis as a public health challenge, while highlighting the impact of the COVID-19 pandemic on underreporting and the subsequent increase in reported cases of drug resistance involving tuberculosis.